Análisis de las prácticas del e-commerce vinculadas al comercio internacional colombiano (2017)
This work aims to demonstrate the importance and competitiveness generated by the economic sector of electronic commerce in Colombia, moderating the actions carried out by the Colombian government for the viability of a correct practice of e-commerce. Beginning with the internet phenomenon, as its appearance in Colombian homes provides the possibility of making payments through an online payment platform. Next, an analysis is made of the increased demand of Colombians when making purchases online and how is the payment method, it is important to highlight the participation of banking entities in the process of banking in the country, to facilitate the use of both debit and credit cards to make international purchases.